2018
DOI: 10.1177/1474904118770818
|View full text |Cite
|
Sign up to set email alerts
|

Higher education for happiness? Investigating the impact of education on the hedonic and eudaimonic well-being of Europeans

Abstract: This study examines the impact of post-secondary education on the well-being of Europeans, comparing single-item hedonic and multi-dimensional eudaimonic models of well-being, operationalized as ‘satisfaction with life’ (SWL) and ‘flourishing’. The results indicate that the impact of education varies significantly when well-being is defined from each of these two perspectives: although vocational education is not significantly associated with the SWL of women and men, it is significantly associated with the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
26
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 81 publications
9
26
0
9
Order By: Relevance
“…The two new variables considered in this study have been marital status and educational level. In this case, the SWLS shows strong invariance between people with higher than high school education and those with a lower educational level, presenting in this sample similar values of satisfaction with their lives, in line with results obtained in previous studies [15,25].…”
Section: Discussionsupporting
confidence: 91%
“…The two new variables considered in this study have been marital status and educational level. In this case, the SWLS shows strong invariance between people with higher than high school education and those with a lower educational level, presenting in this sample similar values of satisfaction with their lives, in line with results obtained in previous studies [15,25].…”
Section: Discussionsupporting
confidence: 91%
“…These findings represent the transitional nature of the population being studied. While the association between wellbeing and higher education is unclear, the findings from the current study suggest personal growth in completing higher education may contribute to emerging adult wellbeing [44]. The association between employment and hedonic wellbeing could be linked to the security and independence enjoyed through full time employment providing the basis for exploring opportunities for pleasure [45,46].…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, there is a need to include other aspects of enabling access such as work experience, career counseling and co-curricular activities as proposed by Pitan (2016). Moreover, World Happiness Report asserts that education has an indirect link to wellbeing through raise of income, increasing the chances of employability and providing secruity of job (Helliwell, Layard, & Sachs, 2012;Jongbloed, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Jongbloed (2018) used data of more than 50,000 individuals form European Social Survey (2012) and found that access to tertiary education was positively and significantly related to subjective wellbeing measured as flourishing. There is a need to retest education and wellbeing link in other countries investigating its differential impact on employed versus unemployed individuals (Jongbloed, 2018).…”
Section: Higher Education and Subjective Wellbeingmentioning
confidence: 99%